Real‐world evidence of biologic treatments in moderate–severe psoriasis in Italy: Results of the CANOVA (EffeCtiveness of biologic treAtmeNts for plaque psOriasis in Italy: An obserVAtional longitudinal study of real‐life clinical practice) study. Issue 1 (23rd November 2021) - Colombo, Delia; Bianchi, Luca; Fabbrocini, Gabriella; Corrao, Salvatore; Offidani, Annamaria; Stingeni, Luca; Costanzo, Antonio; Pellacani, Giovanni; Peris, Ketty; Bardazzi, Federico; Argenziano, Giuseppe; Ruffolo, Silvana; et al.
Abstract: EffeCtiveness of biologic treAtmeNts for plaque psOriasis in Italy: An obserVAtional (CANOVA) study was aimed at providing real‐world evidence of the effectiveness of biologics in Italian patients with moderate–severe psoriasis. It was an observational, retro‐prospective cohort study conducted in 17 Italian dermatology clinics. Adult patients with moderate–severe plaque psoriasis, who started a biologic treatment between 24 weeks and 24 months before enrolment, were included. With a follow‐up visit at 6 months after enrolment, each patient had at least 12 months of observation. The primary objective was to describe the clinical response rates (PASI 75) after 16/24/52 weeks from biologic treatment start. Secondary outcomes were sustained response, quality of life, and treatment satisfaction. Of the 669 eligible patients (64% males), 52% were naïve to biologics, though a mean duration of psoriasis since first diagnosis of 18.6 years ( SD 13.2). The most frequently prescribed biologics were secukinumab (41%), ustekinumab (25%), TNF‐inhibitors (22%) and ixekizumab (12%). PASI 75 was achieved by 86% of patients (95% CI: 82%–89%) at 16 weeks, 90% (87%–93%) at 24 weeks, and 91% (89%–94%) at 52 weeks. Patients achieving PASI 90 and PASI 100 at 52 weeks were 75% (71%–79%) and 53% (49%–57%), respectively. Sustained PASI 75 response after 1 year from treatment start was achieved by 78% (74%–82%) of patients. Mean DLQI total score was 2.3 ( SD 3.9) at enrollment and decreased at the final visit to 1.8 (3.6). A high level of treatment satisfaction was expressed by patients over the study period. This large real‐world study confirms in the clinical practice the good effectiveness and acceptability of biologics in psoriasis patients.